2018
DOI: 10.1002/jctb.5799
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid reactive distillation using polyoctylmethylsiloxane membrane for isopentyl acetate production from mixed PVA by products

Abstract: BACKGROUND The transesterification of methyl acetate and isoamyl alcohol catalyzed by ionic liquids is a new environment‐friendly method for isopentyl acetate (iso‐AmAc) production, and also appropriate for the recovery of polyvinyl alcohol (PVA) byproducts. Therefore, it is of great significance for iso‐AmAc production from PVA byproducts to explore alternative processes with the goal of improving the conversion of the chemical equilibrium reaction and energy efficiency, including reactive distillation (RD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Currently, special distillations such as extractive distillation (ED), heterogeneous azeotropic distillation (HAD), pressure‐swing distillation (PSD) and reactive distillation (RD) are adopted to separate such azeotropes. Arifin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, special distillations such as extractive distillation (ED), heterogeneous azeotropic distillation (HAD), pressure‐swing distillation (PSD) and reactive distillation (RD) are adopted to separate such azeotropes. Arifin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, special distillations such as extractive distillation (ED), 5-8 heterogeneous azeotropic distillation (HAD), [9][10][11][12][13] pressure-swing distillation (PSD) [14][15][16][17] and reactive distillation (RD) [18][19][20][21] are adopted to separate such azeotropes. Arifin et al 22 compared HAD and ED by total annual cost (TAC) to separate the azeotrope IPA + water, and results indicated that ED is more economic than HAD.…”
Section: Introductionmentioning
confidence: 99%